2013
DOI: 10.1080/13548506.2013.769609
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing changes during the menstrual cycle

Abstract: Pain catastrophizing is an important predictor of pain intensity and pain-related outcomes. Many studies have shown that the level of this phenomenon is higher in women compared to men. The aim of this study was to investigate whether there is a difference in pain catastrophizing in women during the different phases of their menstrual cycle and whether there is a difference in pain catastrophizing depending on the history of childbirth and dysmenorrhea. A prospective study was conducted among 149 healthy women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This may have affected pain intensity scores through both response and recall biases, given the cyclical nature of PD. Pain catastrophizing has also been demonstrated to fluctuate during the menstrual cycle [ 62 ], which is consistent with the growing literature on situational versus dispositional catastrophizing [ 63 , 64 ]. Future cross-sectional research should assess participants’ menstrual phase at the time of responding and indeed aim to target phases during which pain is more likely (i.e., menstruation and ovulation phases).…”
Section: Discussionsupporting
confidence: 76%
“…This may have affected pain intensity scores through both response and recall biases, given the cyclical nature of PD. Pain catastrophizing has also been demonstrated to fluctuate during the menstrual cycle [ 62 ], which is consistent with the growing literature on situational versus dispositional catastrophizing [ 63 , 64 ]. Future cross-sectional research should assess participants’ menstrual phase at the time of responding and indeed aim to target phases during which pain is more likely (i.e., menstruation and ovulation phases).…”
Section: Discussionsupporting
confidence: 76%
“…There was also a disproportionate number of participants taking some form of exogenous hormones in the Chronic Pain group as compared with the No Pain group, which may have affected pain responses [43]. Research has suggested elevated levels of pain catastrophizing during menstruation in healthy women [24], so menstruation of some participants at the time of the laboratory assessment may have influenced the results. Our estimate of menstruation at the time of the lab session based on a last menstrual period of 5 days or less from the day of the lab session did not yield any significant differences between the groups so it is unlikely that variation in timing of menstruation accounted for the results.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have shown that women who report higher levels of pain catastrophizing report more severe menstrual pain, compared with those with low levels of pain catastrophizing [23]. Women with dysmenorrhea report higher levels of pain catastrophizing on the first day of menstruation compared with those without dysmenorrhea [24]. No research has yet examined pain catastrophizing and menstrual pain among adolescent girls.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies demonstrated that pain sensitivity varied across the different stages of the menstrual cycle (Isselée, De Laat, Bogaerts, & Lysens, 2001;Wiesenfeld-Hallin, 2005), the more recent, well-controlled studies suggested a lack of variability in pain sensitivity across the different stages of the menstrual cycle (Bartley & Rhudy, 2013;Klatzkin, Mechlin, & Girdler, 2010;Rhudy & Bartley, 2010). Moreover, to our best knowledge, only one published study directly investigated the effect of the menstrual cycle on pain catastrophizing, which showed that pain catastrophizing scores on the 1st, 12th, and 20th days of the menstrual cycle were significantly different (Cosic et al, 2013). However, the authors emphasized that such difference might be confounded by the assessment order, namely, the first measurement of pain catastrophizing was always collected on the first day of the cycle (Cosic et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, to our best knowledge, only one published study directly investigated the effect of the menstrual cycle on pain catastrophizing, which showed that pain catastrophizing scores on the 1st, 12th, and 20th days of the menstrual cycle were significantly different (Cosic et al, 2013). However, the authors emphasized that such difference might be confounded by the assessment order, namely, the first measurement of pain catastrophizing was always collected on the first day of the cycle (Cosic et al, 2013). Therefore, the influence of the menstrual cycle on pain catastrophizing remains to be corroborated.…”
Section: Limitationsmentioning
confidence: 99%